2020
DOI: 10.1101/2020.05.11.20098368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pregnancy and Neonatal Outcomes in SARS-CoV-2 Infection: a systematic review

Abstract: With the emergence of SARS-CoV-2 and its rapid spread, concerns regarding its effects on pregnancy outcomes have been growing. We reviewed 164 pregnancies complicated by maternal SARS-CoV-2 infection across 20 studies. The most common clinical presentations were fever (57.9%), cough (35.4%), fatigue (15.2%), and dyspnea (12.2%). Only 2.4% of patients developed respiratory distress. Of all patients, 84.5% delivered via Cesarean section, with a 23.9% rate of maternal gestational complications, 20.3% rate of pret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
(59 reference statements)
3
13
0
5
Order By: Relevance
“…Our initial search yielded 1132 references. After the initial screening, we assessed the eligibility of 77 full‐text articles; we excluded 25 of them (see Supplementary material, Table ), which led to the inclusion of 52 SRs 7,9,11,21‐69 . Figure 1 provides the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial search yielded 1132 references. After the initial screening, we assessed the eligibility of 77 full‐text articles; we excluded 25 of them (see Supplementary material, Table ), which led to the inclusion of 52 SRs 7,9,11,21‐69 . Figure 1 provides the PRISMA flow diagram.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the SRs were published as journal articles, 7,9,11,22,23,25‐27,29‐36,38‐44,46‐49,51,52,54‐58,61‐67 while some were available as pre‐print articles 21,24,28,37,45,50,53,59,60,68,69 . The SRs were published between 17 March 2020 7 and 4 September 2020 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, several articles have reported that the possibilities of vertical transmission (37,38), highlighting the importance of long-follow up of newborns (39). To clarify the vertical transmission and neonatal outcomes due to SARS-CoV-2 infection; we further compared our findings with other recently published systematic review and meta-analyses (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Raschetti et al (38) evaluated neonatal outcomes from 74 published articles in where 30% of neonates were reported in the possible vertical transmission and 70% were from environmental sources ( Table 4).…”
Section: Comparison With Recent Findingsmentioning
confidence: 98%
“…According to two reports of 18 infected mothers in the third trimester, all neonates tested negative for the COVID-19. Still a baby tested positive who was born from a mother suffering from the COVID-19 in London (Chamseddine et al 2020).…”
Section: Clinical Featuresmentioning
confidence: 99%